2017
DOI: 10.1021/acsnano.7b05442
|View full text |Cite
|
Sign up to set email alerts
|

Highly Luminescent Phase-Stable CsPbI3 Perovskite Quantum Dots Achieving Near 100% Absolute Photoluminescence Quantum Yield

Abstract: Perovskite quantum dots (QDs) as a new type of colloidal nanocrystals have gained significant attention for both fundamental research and commercial applications owing to their appealing optoelectronic properties and excellent chemical processability. For their wide range of potential applications, synthesizing colloidal QDs with high crystal quality is of crucial importance. However, like most common QD systems such as CdSe and PbS, those reported perovskite QDs still suffer from a certain density of trapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
757
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 809 publications
(786 citation statements)
references
References 82 publications
24
757
1
4
Order By: Relevance
“…i‐i) Change of the PL QY of the OA/m−,TOP−CsPbI 3 QDs versus storage time, where QD solutions synthesized at 140 °C were stored in a sealed bottle under ambient conditions. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Optoelectronic Propertiesmentioning
confidence: 99%
“…i‐i) Change of the PL QY of the OA/m−,TOP−CsPbI 3 QDs versus storage time, where QD solutions synthesized at 140 °C were stored in a sealed bottle under ambient conditions. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Optoelectronic Propertiesmentioning
confidence: 99%
“…CsPbX 3 nanocrystals have been incorporated into solar cells achieving a record 13.4 % power conversion efficiency (PCE). [15] Other syntheses have expanded this general idea by generating multiple nanocrystal morphologies through ligand mediation [21][22] and reaction tuning, [23] by using different surface ligands for improved quantum yields, [24][25] by increasing surface passivation/repair via salt solutions, [26][27][28][29] as well as by generating other cation/anion compositions through doping [17,[30][31][32][33][34][35] or post-synthetic ion exchange. [12,[19][20] Most reported syntheses of CsPbX 3 follow the work of Protesescu et al who demonstrated a simple, solution-based synthesis for nanocrystals with high luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…[51] Since CsPbX 3 materials have considerable potential for use in functional devices, the stability of their nanocrystals is of utmost importance. [24] They found the TOP-stabilized nanocrystals show improved quantum yield, and are stable for at least one month under ambient conditions. [15] This phase change is accelerated with harsh washing reagents and, with a more gentle washing strategy-using methyl acetate or MeOAc-CsPbI 3 , is stable in the γ (black) phase for over 2 months.…”
Section: Introductionmentioning
confidence: 99%
“…21 This was explained as triggered by the V Br defects in Cs 4 PbBr 6 samples, which act as “initialization centers”. Although the PLQYs of 10 nm CsPbBr 3 NCs is often found to be in the range of 80–95%, 15,100 it was reported that the formed CsPbBr 3 NCs within the single crystal actually strongly quenches the PL. This is rather contradictory as one would expect an increase in the PLQY when CsPbBr 3 NCs are formed.…”
mentioning
confidence: 99%